Peningkatan Kompetensi Guru dan Siswa SMK Melalui Bimtek Penyusunan Laporan Keuangan Berbasis SAK-ETAP - Reni Endang Sulastri; Ferdawati Ferdawati; Welsi Haslina; Reno Fithri Meuthia; Vioni Hidayati (Jurnal Informasi Pengabdian Masyarakat, 2023)
The main competency that must be possessed by vocational school students majoring in accounting is competency in preparing financial reports, namely competency as an "Accounting Technician". The achievement of this scheme for accounting technicians is through two clusters, namely the preparation of financial reports based on the Financial Accounting Standards for Entities Without Public Accountability (SAK ETAP) and the operation of accounting computer applications. During the competency test held in February 2023, there were still many students at SMKN 1 Padang Panjang who were not yet competent in the SAK ETAP-based financial report preparation cluster. The aim of this service is to provide technical guidance on preparing financial reports based on SAK ETAP for teachers and students majoring in accounting at SMKN 1 Padang Panjang so that their main competencies are fulfilled. The methods used are technical guidance and assistance in working on practice questions and also carrying out simulations or tryouts for competency exams in preparing SAK ETAP-based financial reports as well as evaluation of the activities that have been carried out. The service team will also provide updated reference books to partners along with modules and a comprehensive collection of questions. With this service, it is hoped that it can increase students' competence in preparing financial reports so that during the accounting technician certification exam later at SMKN 1 Padang Panjang the percentage of passes will be high. Apart from that, this service can also increase teacher competence in teaching the preparation of SAK ETAP-based financial reports to students.